Peningkatan Produktivitas Padi Melalui Penerapan Jarak Tanam Jajar Legowo - Ikhwani Ikhwani; Gagad Restu Pratiwi; Eman Paturrohman; A. K. Makarim (Puslitbang Tanaman Pangan, 2013)
Rice productivity in the irrigated wet land could be increased by applying the best cultivation practices. Pair rows vis a vis square plant spacing is capable of increasing rice productivity, due to higher plant population and better plant orientation to utilize the solar radiation. Rice yield could be further improved through the varietal selection among the Inpari series (Inpari-14, 15, 18 and 19) to identify which one is the most adaptable to higher plant density. The minimum grain yield per hill of the pair rows was determined in order to identify rice variety or fertilizer rate which could yield more compare to that of square plant spacing. Plant hill with smaller number of tillers is expected to be suitable for pair rows planting. When plant hill has many tillers due to the varietal type or fertile soil, wider spacing of double pair rows, such as 4:1 (25-50 cm) x 12.5 cm is suggested. The introduction of pair rows or double pair rows initially was not well accepted by farmers due to the higher seed requirement and higher labor cost when compared to that of the square plant spacing. However, the pair-rows spacing has been accepted now due to a better and easier in crop protection and fertilizer application. In a large farming scale, pair rows planting requires the support of machines as the a planting tool which is adjustable to desired plant spacing, durable and easy to operate. Rapid varietal identification to select suitable varieties for pair rows planting is needed in order to provide advice to farmers of the optimum plant spacing for each particular variety.